Design of Electrode Placement for Presenting Phosphenes in the Lower Visual Field Based on Electric Field Simulation - Manami Kanamaru (MDPI AG, 2021)
Presenting visual information, called phosphenes, is a critical method for providing information on the position of obstacles for users of walking support tools for the visually impaired. A previous study has established a method for presenting phosphenes to the right, center, and left of the visual field. However, a method for presenting information on the position of obstacles around the feet using phosphenes, which is essential for the visually impaired, has not been clarified. Therefore, in this study, a method for presenting phosphenes in the lower visual field is presented, towards the aim of realizing a safe walking support tool. Electrode placement is proposed in this paper for the presentation of phosphenes to the right, center, and left of the lower visual field based on the electrode placement method used in the previous study, which presents the phosphene in three locations of the visual field. In addition, electric field simulation is performed, focusing on the electric field value on the eyeball surface, in order to observe whether the proposed electrode placement is able to stimulate the intended region. As a result, it is shown that the intended region on the eyeball surface can be stimulated locally with each of the proposed electrode placements.